2020
DOI: 10.1002/cam4.3079
|View full text |Cite
|
Sign up to set email alerts
|

CAG regimen for refractory or relapsed adult T‐cell acute lymphoblastic leukemia: A retrospective, multicenter, cohort study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…2,7 In previous studies, CAG regimen (aclarubicin, cytarabine [Ara-C], and granulocyte colony-stimulating factor [G-CSF]), a widely used treatment for acute myeloid leukemia in East Asia, is highly effective in the treatment of refractory or relapsed (R/R) T-ALL patients. 8,9 Decitabine has been demonstrated to be effective therapies for treating myeloid neoplasms. In addition to the potential direct antileukemia effects in ETP-ALL, preclinical studies have shown that decitabine may have synergistic effects with conventional chemotherapy agents in vitro.…”
Section: Salvage Therapy With Decitabine In Combination With Granulocmentioning
confidence: 99%
“…2,7 In previous studies, CAG regimen (aclarubicin, cytarabine [Ara-C], and granulocyte colony-stimulating factor [G-CSF]), a widely used treatment for acute myeloid leukemia in East Asia, is highly effective in the treatment of refractory or relapsed (R/R) T-ALL patients. 8,9 Decitabine has been demonstrated to be effective therapies for treating myeloid neoplasms. In addition to the potential direct antileukemia effects in ETP-ALL, preclinical studies have shown that decitabine may have synergistic effects with conventional chemotherapy agents in vitro.…”
Section: Salvage Therapy With Decitabine In Combination With Granulocmentioning
confidence: 99%
“…T‐cell acute lymphoblastic leukemia (T‐ALL) is a highly aggressive leukemia with poor clinical outcome, and there is currently no effective or targeted therapy for this disease 1–5 . Despite intensive chemotherapy or hematopoietic stem cell transplantation (HSCT) being used for T‐ALL, less than 50% of adults and 75% of children with T‐ALL have a 5‐year overall survival (OS), particularly for relapsed patients 1,6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…T‐cell acute lymphoblastic leukemia (T‐ALL) is a highly aggressive leukemia with poor clinical outcome, and there is currently no effective or targeted therapy for this disease. 1 , 2 , 3 , 4 , 5 Despite intensive chemotherapy or hematopoietic stem cell transplantation (HSCT) being used for T‐ALL, less than 50% of adults and 75% of children with T‐ALL have a 5‐year overall survival (OS), particularly for relapsed patients. 1 , 6 , 7 , 8 However, the pathogenesis of T‐ALL is relatively complex, mainly due to T‐cell receptor (TCR) rearrangement during the development and differentiation of T‐cells, which easily results in gene alterations by unstable factors.…”
Section: Introductionmentioning
confidence: 99%